Gender Representation in Indonesian ELT Textbooks of Junior High School: A Corpus-Assisted Critical Discourse Analysis - Fidyaningsih, Adhes; Oktavianti, Ikmi Nur (Institut Agama Islam Negeri Palopo, 2024)
This study explores gender representation in Indonesian English Language Teaching (ELT) textbooks for Junior High School under the Merdeka Curriculum, employing a corpus-assisted Critical Discourse Analysis (CDA) approach. The research identifies gender-related references and analyzes positive and negative character constructions. The findings indicate a persistent gender imbalance, with male references appearing more frequently than female references in categories such as famous names, fictional names, ordinary names, and pronouns. Male characters are often portrayed with a mix of positive and negative traits, while female characters are predominantly depicted in a positive light. The study concludes that while progress has been made, there is still a significant need for more balanced and inclusive gender representation in educational materials. Addressing these imbalances is crucial for creating an equitable learning environment that reflects and promotes gender equality.